Species conflict at Earth’s edges – Contests, climate, and coveted resources - Berger, Joel; Biel, Mark; Hayes, Forest P. (Frontiers in Ecology and Evolution, 2022)
Direct conflict between species is an infrequently witnessed biological phenomenon. Potential drivers of such contests can include climate change, especially at Earth’s high elevation and latitudinal extremes where temperatures warm 2-5 times faster than elsewhere and hydro-geomorphic processes such as glacial recession and soil erosion affect species access to abiotic resources. We addressed a component of this broader issue by empirical assessments of mammalian conflict over access to four abiotic resources – minerals, water, snow, and shade – by annotation of past studies and by empirical data collection. Evidence for Nearctic and Palearctic mammals suggestsindicates that when desert waters are in short supply, contests intensify, generally favoring larger species regardless of their status as native or exotic. Our empirical data indicate that contests between two large and approximately similarly-sized mammals – mountain goats (Oreamnos americanus) and bighorn sheep (Ovis canadensis) – along a 2,500 km gradient at three high-altitude (above tree-line) sites in the Rocky Mountains of North America, result in striking asymmetries; goats dominated >95% of interactions. Despite far fewer observations of encounters to access shade or snow patches, an increasingly prominent dialog needs to be held about rarely explored biological phenomena where less is known than we might otherwise presume, whether induced by climate or increasing anthropological alteration because of underpinnings to understand community structure and conservation planning. Observations on the frequency and intensity by which individuals escalate behavior to access abiotic resources remains an underappreciated arena to help identify the proximate importance of scarcity in the natural environment. Notwithstanding Darwin’s (1859) prediction some 165 years ago that populations in extreme environments (high-latitude, high-altitude) are more likely to be impacted by abiotic variables than biotic, conflict between species such as contest competition may be reflective of climate degradation coupled with the changing nature of coveted resources.